Experimental investigation into load settlement characteristics of piled rafts in sand - Leong, Hazel Xueling. (2011)
When the loads of buildings were not excessively large, shallow foundations such as rafts were preferred. However, in most of these cases, the foundation system would settle very much, and cause serviceability problems. To improve on this, Burland et al. (1977) first proposed the concept of adding piles to rafts about 30 years ago. Studies by many notable researchers in the years to come suggest that the most effective combinations of piles and raft happens when all the initial loading can be borne with the raft’s bearing capacity alone. The role of the piles was solely to reduce the excessive settlement experienced by the plain raft.